Webinar Panelist RPCPE Serial Response to Pandemic Covid-19 - Hari Kusnanto Josef; Dhanasari Vidiawati; Elsa Pudji Setiawati; Mariatul Fadilah; Armyn Nurdin; Syarhan Syarhan; Sintak Gunawan; Mora Claramita (Faculty of Medicine, Public Health, and Nursing, 2022)
Relaxation of PSBB Policy from the Perspective of Community Medicine and Epidemiology in IndonesiaWhen the government will do something meaningful and full of uncertainty, such as relaxation of the PSBB, it needs to be done based on a plan with uncertainty, namely scenario planning. In scenario development, four stages must be carried out, namely identifying the driving forces and critical uncertainties. Some scenarios then create a path for how a plan will travel.